English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1.Find the slope of the line through (-3, -2) and (-5, 3)

2.Find the slope and y-intercept: 3x + y = 2

3. Write in slope intercept form: 4x + 6y = 5

4.Solve the system:
x + y + z = 4
x - y + z = -2
2x + y - z = 2

5. Simplify:

(14x – 7) / (2x – 1)

6.Simplify:

(x2 - 8x + 16) / (x2 – 16)

2006-12-21 03:45:40 · 13 answers · asked by wil46yang 2 in Science & Mathematics Mathematics

13 answers

1.Find the slope of the line through (-3, -2) and (-5, 3)
(3-(-2) )/ (-5 - (-3)) = 5/-2 = -2/5

2.Find the slope and y-intercept: 3x + y = 2
slope= -3
y= -3x+2,
y-intercept= 2

3. Write in slope intercept form: 4x + 6y = 5
6y= -4x +5
y= -4x/6 + 5/6
y= -2x/3 + 5/6

6.Simplify:

(x2 - 8x + 16) / (x2 – 16)= (x-4)(x-4)/(x-4)(x+4)
= (x-4)/(x+4) .

2006-12-21 04:10:24 · answer #1 · answered by Anonymous · 3 0

1. *You need to know the slope formula:
m = (first y - second y)/(first x - second x)
*Take the points and place them into the formula and solve...

2. 3x + y = 2

First: solve for "y" > subtract 3x from both sides (opposite side means opposite sign):

3x - 3x + y = -3x + 2
y = -3x + 2

Second: the slope is a number/fraction in front of the "x" >
>> slope = -3. The y-intercept is the whole number after the "x" variable >>> y-int = 2

3. give it a try

5. factor the numerator and factor the denominator > take out a common factor from the top and do the same for the bottom:

= [7(2x - 1)]/[1(2x -1)]

*cancel "like" terms > cancel (2x -1) from the top and bottom

= 7

6. give it a try

2006-12-21 13:42:26 · answer #2 · answered by ♪♥Annie♥♪ 6 · 1 0

1) Slope =[3-(-2)]/[-5-(-3)] = 5/-2 = -5/2 Ans
2) 3x + y = 2
y = -3x+2
Slope = -3
y - intercept = 2 Ans

3) 4x + 6y = 5
6y = -4x +5
y = (-4/6)x +5/6
y = (-2/3)x +5/6 Ans

4) x+y+z = 4.............A
x-y+z = -2..............B
2x+y-z = 2.................C
B + C gives
3x = 0 ; x= 0
A + B gives
2x+2z = 2 ; 2z = 2 gives z= 1
x+y+z = 4
y = 4-1 =3

The solution is
x= 0; y = 3 ; z = 1 Ans

5) (14x-7)/(2x-1) = 7(2x-1)/(2x-1) = 7

6) (x^2-8x + 16) / x^2-16) = (x - 4)^2 / [(x+4)(x-4)
= (x-4) / (x+4) Ans

2006-12-21 12:17:35 · answer #3 · answered by ATS 2 · 1 0

1. Slope of line= m =(y2-y1)/(x2-x1)= (3+2)/(-5+3) = -5/2

2. y=2-3*x.........thus,slope=-3 , y-intercept=2

3. y = -2x/3 + 5/6

4. x=0,y=3,z=1.....by solving simultaneously

5. (14x – 7) / (2x – 1) = 7*(2x – 1)/(2x – 1) = 7 ....iff x is not= 1/2

6. (x2 - 8x + 16) / (x2 – 16)= (x-4)^2/(x+4)(x-4)
= (x-4)/(x+4) .... iff x is not = 4

2006-12-21 11:47:45 · answer #4 · answered by Som™ 6 · 3 0

1.
(3-(-2) )/ (-5 - (-3)) = 5/-2 = -2/5

2.
slope= -3
y= -3x+2,
y-intercept= 2

3.
6y= -4x +5
y= -4x/6 + 5/6
y= -2x/3 + 5/6

6.
(x2 - 8x + 16) / (x2 – 16)= (x-4)(x-4)/(x-4)(x+4)
= (x-4)/(x+4) .

2006-12-22 11:45:38 · answer #5 · answered by lobis3 5 · 0 0

\6\ (x-4)^2 / (x-4) / (x+4) = (x-4)/(x+4);
/5/ 7(2x-1) / (2x-1) = 7;
\4\ add the 2nd to the 3rd; thus the 3rd looks: 3x=0, hence x=0; now substitute 0 instead of x into 1st and 2nd;
thus y+z=4
and –y+z=-2;
add them; thus 2z=2, hence z=1 and y=3;
/3/ y=-(4/6)*x + (5/6) = (-2/3)*x + (5/6), (-2/3) being slope to x-axis, (5/6) being intercept of y-axis; or x=-(3/2)*y + (5/4), (-3/2) being slope to y-axis, (5/4) being intercept of x-axis;
\2\ y=-3x+2, -3 being the slope to x-axis, +2 being y-intercept;
/1/ the line through them: (y-y1) = {(y2-y1)/(x2-x1)} * (x-x1), the slope being (y2-1)/(x2-x1) = (3+2)/(-5+3) = -5/2;

2006-12-21 12:35:42 · answer #6 · answered by Anonymous · 1 0

1

2006-12-21 11:49:41 · answer #7 · answered by BigMack 2 · 0 5

Lazy bastard. I will tell you how to do these problems but I won't do them for you, they are so simple.

1. Graph it, use rise/run method to calculate the slope.

2. Slope intercept form is y = mx + b. Solve this equation for y to get it into that form. m is your slope, b is your y intercept.

3. Slope intercept form is y = mx + b. Get the equation into that form by solving for y. m is your slope, b is your y intercept.

4. You can solve this any way you want. First solve for one variable by isolating it to one side, then plugin the solution to that variable into another equation. Repeat this until you eliminate variables to solve for.

5. FOIL, First Inner Outer Last. 14x * 2x = First. -7 * 2x = Inner. 14x * -1 = Outer. -7 * -1 = Last.

6. Factor (x^2 - 8x + 16), then apply FOIL to the factored equation. Then divide by what's on bottom.

2006-12-21 11:59:34 · answer #8 · answered by Anonymous · 2 2

1)(-3,-2),(-5,3)
Slope:m=(y2-y1)/(x2-x1)
m=(3+2)/(-5+3)=-5/2

2)3x+y=2
Subtract 3x from both sides:
y=-3x+2
Slope=-3,y-intercept:2

3)4x+6y=5
Slope-intercept form:
y=mx+b
Subtract 4x from both sides:
6y=-4x+5
Divide 6 from both sides:
y=-2/3x+5/6

4)
x+y+z=4
x-y+z=-2
=======
2x+2z=2

x-y+z=-2
2x+y-z=2
=======
3x=0
x=0

2(0)+2z=2
2z=2
z=1

0+y+1=4
y+1=4
y=3
(0,3,1)

Check:
0+3+1=4
4=4

0-3+1=-2
-2=-2

2(0)+3-1=2
2=2

5)(14x-7)/(2x-1)
7(2x-1)/(2x-1)=7

6)(x^2-8x+16)/(x^2-16)
(x-4)(x-4)/(x-4)(x+4)=
x-4/x+4

I hope this helps!

2006-12-21 12:03:46 · answer #9 · answered by Anonymous · 1 0

(-3,-2)and (-5,3)
we know that m=y2-y1/x2-x1
Here X1=3 X2=-5 and Y1=-2,and Y2=3
so Slope M= Y2-Y1/X2-X1
= 3-(-2)/-5-(-3)
=5/-2 Becouse --is +
so slope =-5/2
3x+Y=2
we know that Y=mx+C
so Y=-3x+2
so M=-3
and x+Y+Z=4-----(1)
X-y+Z=-2 ------(2)
2x+Y-z=2------(3)
Adding Eq (1)and (2)
2x+2Z=6
X+Z=3-----(4)

2006-12-21 12:17:48 · answer #10 · answered by Raja 1 · 1 0

fedest.com, questions and answers